Manufacture and characterization of optimized red ginseng drinks containing herbal medicine extracts - Kim, Hak-Jung; Baik, Moo-Yeol; Yang, Byung-Wook; Kim, Hae-Kyung; Kim, Byung-Yong (Food science and biotechnology, 2019)
The optimum mixing ratio of red ginseng, herbal medicine extracts, and oligosaccharides for diabetic improvement was investigated and verified through animal experiments. Using the optimum mixing technique, 2% red ginseng extract, 15% oligosaccharides, and 83% herbal medicine extracts were determined to be optimal for red ginseng beverages. The taste was improved as the amount of red ginseng decreased and oligosaccharides increased, whereas antioxidative activity was increased with increased red ginseng. In the animal model in which streptozotocin was administered to BALB-c mice, the red ginseng administration group exhibited lower blood glucose than the diabetic control group, and the blood glucose level was lower in the herbal medicine and red ginseng extract administration group. Insulin concentration was slightly increased by the red ginseng beverage, and hepatotoxicity due to excessive intake of red ginseng beverages was not detected.